Pull - Binns, B. A. (Lodi, NJ : WestSide Books, 2010)
After his father kills his mother, seventeen-year-old David struggles to take care of his two sisters--and himself--while dealing with his grief, guilt, and trying to fit in at a tough new school while hiding his past.
Young Adult.
Young Adult
Keywords: African Americans -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Guilt -- Juvenile fiction; High schools -- Juvenile fiction; Orphans -- Juvenile fiction; Schools -- Juvenile fiction; African Americans -- Fiction; Brothers and sisters -- Fiction; Coming of age -- Fiction; Guilt -- Fiction; High schools -- Fiction; Orphans -- Fiction; Schools -- Fiction; African Americans -- Fiction; Bildungsromans; Guilt -- Fiction; High schools -- Fiction; Orphans -- Fiction; School stories; Siblings -- Fiction; Chicago (Ill.) -- Juvenile fiction; Chicago (Ill.) -- Fiction; Chicago (Ill.) -- Fiction; Bildungsromans